First in Vivo SPECT Imaging of Mouse Femorotibial Cartilage Using Tc-NTP 15-5 - Elisabeth Miot-Noirault; Aurélien Vidal; Philippe Auzeloux; Jean-Claude Madelmont; Jean Maublant; Nicole Moins (Molecular Imaging)
This study aimed to report the first single-photon emission computed tomographic (SPECT) imaging of articular cartilage in mice using 99m Tc-NTP 15-5 radiotracer. Mice intravenously injected with 99m Tc-NTP 15-5 were submitted to (1) dynamic planar imaging, (2) static planar imaging, (3) 1 mm pinhole SPECT acquisition, and (4) dissection. Tomographic reconstruction of SPECT data was performed with a three-dimensional ordered subset expectation maximization algorithm, and slices were reconstructed in three axes. 99m Tc-NTP 15-5 rapidly accumulated in the joint, with a peak of radioactivity being reached from 5 minutes postinjection and maintained for at least 90 minutes. Given that bone and muscle did not show any accumulation of the tracer, highly contrasted joint imaging was obtained from 15 minutes postinjection. When 1 mm pinhole SPECT acquisition was focused on the knee, the medial and lateral compartments of both the femoral condyle and tibial plateau were highly delineated, allowing a separate quantitation of tracer accumulation within each component of the femorotibial joint. A good correlation was found between tracer uptake determined by region of interest analysis of both planar and SPECT scans and dissection. This new approach to imaging of cartilage in mice provides joint functionality assessment in vivo, giving a unique opportunity to achieve a greater understanding of cartilage physiology in health and disease.